The Forty-Four Hours Case in Australia, 1926-1927 - de R. Foenander, O. (Quarterly Journal of Economics, 1928)
I. Introductory, — II. The Issue and its Joinder, 308. — III. Judgment delivered, 311. — The Opinions of Lukin and Beeby, 312. — The Opinion of the Chief Judge, 314. — IV. Evidence on Australian Productivity before and after the War, 319. — V. The Judgment and the Fiscal Policy of Australia, 321. — VI. Indications of the attitude of the Court on subsequent applications, 322. — VII. Decisions on subsequent applications of 1927, 325.